Philippine Cigarette Excise Tax Revenues under Two Tax Systems - Sicat, Charlotte Justine D. (Philippine Management Review; Vol 23 (2016), 2016)
The Philippines had two types of cigarette excise taxes in the past three decades: an ad valorem tax under the 1986 Tax Reform Program (TRP) and a specific tax under the 1997 Comprehensive Tax Reform Program (CTRP). Ad valorem taxes, according to economic theory, are desirable since these are flexible in that tax revenues automatically adjust to price changes. However, economic theory also recognizes the difficulty in implementing ad valorem taxes because of the challenge in identifying the appropriate tax base (e.g., price). The alternative, a specific tax is easier to implement but is not flexible, requiring regular adjustments in taxes to inflation. In practice, this characteristic of flexibility is even more important if the political or institutional environment make it difficult to increase existing or pass new tax laws. Empirically, Philippine cigarette excise tax revenues—in real terms—declined in the period after the shift to a specific tax. This study examines the effect of a shift from an ad valorem to a specific cigarette excise tax on Philippine cigarette excise tax collections during the period 1988 to 2005. The results showed a significant negative relationship between cigarette excise tax revenue effort and the period when a specific excise tax was in effect. Though the results cannot entirely attribute the decline in cigarette excise tax effort to the 1997 CTRP shift to specific taxes because of politico-institutional reasons (e.g., not implementing the provisions of the law), the results showed that Philippine cigarette excise tax effort is negatively related to the 1997 CTRP.
Keywords: tax policy, sin tax, cigarette excise tax